Controlling pandemic flu - Oxford, John (Henry Stewart Talks, 2013)
The power of infection, Three levels of protection, The influenza virus, The influenza vaccine, Anti-viral drugs, The three faces of hygiene, 2009 swine flu outbreak, Flu pandemics, years of life lost, Bird flu, The common cold clinic – influenza research in Retroscreen virology, Influenza virus components, The 1918 flu pandemic, Researching the new virus on the front, What’s needed for an influenza virus to emerge?, Researching the 1918 virus, The pandemic window of 1918, New aspects into modern science